Estimation of the Chlorophyll –a and Phaeophytin - a and Their Vertical Distribution in Sediment of the Shatt al-Arab River South Iraq - Al-Shaheen, Maitham A. (Iraqi Journal of Aquaculture, 2021)
Current study estimates Chlorophyll – a and Phaeophytin - aand their vertical distributed to a depth ten centimeters in the sediments of Shatt Al-Arab riverfor five stations from Al-Maakal to Fao city for the period from February to November 2013.The upper centimeters, especially the first centimeterwas marked by the highest concentrations of the chlorophyll - apigment in all stations for most of the study period, while the lower values have been recorded in the lower centimeters except for a few exceptions. The highest concentrations of both pigments was in the first station, the highest concentrations of chlorophyll - a 79.833 μg/g during April for the first centimeter, while the highest concentrations of phaeophytin - a 51.706 μg/g during October at first centimeter. The lowest concentrations of chlorophyll –awas in the second station, reaching 0.101 μg/g in April, while the lowest concentrations of Phaeophytin - a0.026 μg/gwas at sixth centimeter during May atfourth station.In general, the first stationwas marked bythe highest concentrations of Chlorophyll – arecorded during whole the study period, while the fifth station had recorded the lowest concentrations.